The Implication of Sustainable Development Goals on Sustainable Fishery Management Policy - Masitha Tismananda; Titik Suharti (CV. Science Tech Group, 2025)
The Sustainable Development Goals (SDGs) contain seventeen goals that must be achieved by all United Nations (UN) member states by 2030. The goals to be achieved in order to realize sustainable development also include the marine and fisheries sector. Fisheries management policies of countries should be made by taking into account the SDGs in the marine and fisheries sector so that their implementation can encourage the realization of sustainable development. There are two problems studied in this paper, First, the background or philosophical basis for the preparation of the SDGs by states. Second, how the direction of sustainable fisheries management policies by states is based on the SDGs. This study uses a normative research method with an explanation and descriptive method. This study found that considering the content of the SDGs, states seek to advance several elements at once in achieving sustainable development. The elements are people, planet, prosperity, peace, and cooperation. State policies on sustainable fisheries management should consider the goals in the SDGs that have been adopted, especially Goals 1,2,6,12,13, and 14. Such policies are in line with international law and will be able to contribute to the fulfillment of the 17 Goals of the SDGs.